Living stories of the Cherokee - Duncan, Barbara R.; Arch, Davey (University of North Carolina Press, 1998)
This book, the first major new collection of Cherokee stories published in nearly a hundred years, presents seventy-two traditional and contemporary tales from the Eastern Band of Cherokee Indians in North Carolina. It features stories told by Davey Arch, Robert Bushyhead, Edna Chekelelee, Kathi Smith Littlejohn, and Freeman Owle - five Cherokee storytellers who learned their art and their stories from family and community. The collection also includes a story presented in the Cherokee language and syllabary, translated by tribal interpreter Marie Junaluska. The tales gathered here include animal stories, creation myths, legends, and ghost stories as well as family tales and stories about events in Cherokee history.